The Implementation of In-Service Teacher Professional Education for Improving the Quality of Education in Indonesia: An Analysis of Digital Public Opinion - Sari, Iis Indah; Munawar, Fuad; Supiana, Supiana (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
The purpose of this study is to analyze the extent of public perception of the implementation of the PPG program in the context of Indonesian education. This study uses a qualitative method using a deductive-inductive approach, data collection with web scraping techniques. The criteria for selecting data from comments are by selecting relevant and representative comments that include various views on the implementation of the Teacher Professional Program. The analysis technique used is to use text-based analysis to assess whether a comment is positive, negative or neutral supported by various references such as books, journal articles, and relevant references. The data in this study was taken from a post on Instagram entitled "Pros and Cons in PPG In-Position" on the @infoppg.id account. The reality is that the implementation of PPG is still reaping pros and cons caused by the lack of transparency in the implementation of the program. Tujuan dari penelitian ini yaitu menganalisis sejauh mana realita persepsi masyarakat mengenai pelaksanaan program PPG dalam konteks pendidikan Indonesia. Penelitian ini menggunakan metode kualitatif dengan menggunakan pendekatan deduktif-induktif, pengumpulan data dengan teknik web scraping. Kriteria pemilihan data dari komentar dengan cara memilih komentar yang relevan dan representatif yang mencakup berbagai pandangan mengenai pelaksanaan Program Profesi Guru. Teknik analisis yang digunakan yaitu menggunakan analisis berbasis teks untuk menilai apakah suatu komentar bersifat positif, negatif atau netral dengan didukung berbagai referensi seperti buku, artikel jurnal, dan referensi yang relevan. Data pada penelitian ini diambil dari sebuah postingan di Instagram yang berjudul â€œPro dan Kontra dalam PPG Dalam Jabatanâ€ pada akun @infoppg.id. Realitanya pelaksanaan PPG masih menuai pro dan kontra yang disebabkan oleh kurangnya transparansi pelaksanaan program.